Controllable growth of multilayered XSe2 (X = W and Mo) for nonlinear optical and optoelectronic applications. (17th November 2021) - Ye, Kun; Liu, Lixuan; Chen, Liying; Li, Wenlong; Wang, Bochong; Nie, Anmin; Xiang, Jianyong; Zhai, Kun; Wen, Fusheng; Mu, Congpu; Zhao, Zhisheng; Gong, Yongji; et al.
Abstract: The layered transition metal dichalcogenides (TMDs) exhibit the intriguing physical properties and potential application in novel electronic devices. However, controllable growth of multilayer TMDs remains challenging. Herein, large-scale and high-quality multilayer prototype TMDs of W(Mo)Se2 were synthesized via chemical vapor deposition. For Raman and photoluminescence measurements, 2H and 3R multilayer WSe2 crystals displayed significant layer-dependent peak position and intensity feature. Besides, different from the oscillatory relationship of second harmonic generation (SHG) intensity for odd–even layer numbers in 2H-stacked multilayer WSe2, the SHG intensity of 3R-stacked ones parabolically increased with the thickness due to the absence of inversion symmetry. For device application, photodetectors based on WSe2 with increasing thickness exhibited p -type (bilayer), ambipolar (trilayer), and n -type (four layers) semiconductor behaviors, respectively. Furthermore, photodetectors based on the as-synthesized 3R-stacked WSe2 flakes displayed an excellent responsivity of 7.8 × 10 3 mA W −1, high specific detectivity ( Da * ) of 1.7 × 10 14 Jones, outstanding external quantum efficiency of 8.6 × 10 2 %, and fast response time ( τ Rise = 57 ms and τ Fall = 53 ms) under 532 nm illumination with bias voltage of V ds = 5 V. Similar results have also been achieved in multilayer MoSe2 crystals. All these findings indicate great potential of 3R-stacked TMDs in two-dimensional optoelectronic applications.